Masjid Bengkok : Kajian Sejarah Sosial dan Kontribusi Terhadap Masyarakat di Kota Medan - Abdul Gani Jamora Nasution; Fitri Yanti Pasaribu; Ardila Sari; Fachrizal Alwi; Dwika Aulia Fitrah P. (Prodi Perpustakaan dan Sains Informasi, 2022)
The mosque is an important place for religious activities for Muslims, including the Old Alley Mosque. Gang Bengkok Mosque was established in 1874, and is the second oldest mosque in Medan city after the Osmani Mosque which was founded in 1854. This mosque was founded by four important people namely: Datuk M. Ali (As Agnia), Syeikh Muh. Yacub (Mandailing leader as a scholar), Tjong A Fie (Contributing to the finances for the construction of the mosque), Mufthi Syeikh Hasan Maksum (Allowing the construction of the mosque). The purpose of building this mosque, among others, is to provide awareness of religious people to make religious values ​​an important aspect. The Old Gang Bengkok Mosque contributes to society, especially in terms of the state, namely, as a sign of the Indonesian nation's struggle in terms of moving the hearts of Muslims to jihad and creating tolerance towards religious people, because the foundation of the construction of this mosque is so that religious people can respect each other. This research was conducted by means of observation and interviews